2019
DOI: 10.1002/fsn3.927
|View full text |Cite
|
Sign up to set email alerts
|

Optimization on production of konjac oligo‐glucomannan and their effect on the gut microbiota

Abstract: Konjac glucomannan (KGM) is a polysaccharide extracted from Amorphophallus konjac, and its degradation product is konjac oligo‐glucomannan (KOG). The aim of this study was to produce KOG from KGM and to evaluate its effect on the gut microbiota in fecal batch culture. KOG was produced by enzymatic hydrolysis using β‐mannanase. The optimum conditions were as follows: reaction temperature of 48°C, reaction time of 4 hr, pH of 5.5 and E/S of 0.05% followed by purification step using 3,000 NMWC ultrafiltration (UF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…In hydrolysis, the activity and stability of enzymes are different depending on typical of buffer composition for maintaining pH in the reaction (Liu et al, 2015). As a result, a pH of 5.5 of acetate buffer was a value reasonably well with literature previously demonstrated by Ariestanti et al (2018) and favored with the company requirement of enzyme used.…”
Section: Effect Of Ph On Pog Productionsupporting
confidence: 80%
See 1 more Smart Citation
“…In hydrolysis, the activity and stability of enzymes are different depending on typical of buffer composition for maintaining pH in the reaction (Liu et al, 2015). As a result, a pH of 5.5 of acetate buffer was a value reasonably well with literature previously demonstrated by Ariestanti et al (2018) and favored with the company requirement of enzyme used.…”
Section: Effect Of Ph On Pog Productionsupporting
confidence: 80%
“…The result showed oligosaccharides were not obtained within 2 h incubation at 28 o C but increasing gradually incubatiom time during 6-12 h. It was contrary to the trend at 37 o C and 48 o C. However, the depolymerization of PGM at 37 o C took time very quickly after 2 h and elevating gradually during incubation time while no producing the oligosaccharide at 48 o C was observed after 2 h. The oligosaccharides (%) at 37 o C showed significantly increased (p<0.05) after 2 h and kept maintained during 12 h. Oligosaccharides were produced under the prediction of optimum temperature in a short period incubation time compared to one of the treatments described above (48 o C). It was according toAriestanti, et al (2018) reported the highest concentration of oligosaccharide production with lower molecular weight was at the condition of 48 o C…”
mentioning
confidence: 98%
“…Acetate, as the metabolite of Prevotella_9, played a vital role in preventing multiple sclerosis. Glucomannan and its degradation product oligo-glucomannan had been proved to increase the production of butyrate [ 46 ]. A negative correlation between Bacteroides and butyrate was found within in vitro trials [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Bacteroides were reduced after 72 h for all substrates, while clostridia were reduced after 24 h for LKOG and inulin and after 12 h for KGM and PGM. As a final result, the authors underlined that LKOG was selectively fermented by beneficial bacteria, with a higher butyrate production [93].…”
Section: New Molecules With Prebiotic Effectsmentioning
confidence: 96%